On a vibration problem of homogeneous string - Figueroa-López, Rodiak N. (2018)
In this paper we study the existence and uniqueness of the weak solution of a mathematical model that describes the vibration of a string. This model is given by a wave equation with dynamic boundary conditions. Also, we show that this model is conservative but is not exponentially stable.